Medication Adherence Remains a Challenge Among Hypertensive Patients in Primary Healthcare: Evidence from West Java, Indonesia - Hardini Tri Indarti; Melati Amalia Putri; Yosvi Sayyidah Muslima; Sri Atun; Siti Aminah; Euis Setiawati (Master Program of Health Promotion Faculty of Public Health Diponegoro University, 2026)
Background: Hypertension is a chronic disease that requires long-term treatment to prevent cardiovascular complications. Medication adherence plays a crucial role in blood pressure control; however, adherence remains suboptimal among many patients. This study aimed to examine the association between patient characteristics and medication adherence among hypertensive patients in primary healthcare settings.Method: A cross-sectional study was conducted in April 2026 at Batujajar Primary Health Center, West Bandung Regency, and a primary clinic in Cimahi City, Indonesia. A total of 178 hypertensive patients were recruited using total sampling. Data were collected using a respondent characteristics questionnaire and the Indonesian version of the 8-item Morisky Medication Adherence Scale (MMAS-8). Data were analyzed using Chi-square tests and binary logistic regression, with a significance level of p<0.05.Result: Only 26.4% of respondents were categorized as adherent to antihypertensive medication. Bivariate analysis showed significant associations between age (p=0.019), educational level (p=0.017), duration of hypertension (p=0.012), and medication adherence. Younger patients, those with higher educational attainment, and those who had lived with hypertension for at least five years demonstrated higher adherence rates. Sex was not significantly associated with medication adherence (p=0.405). In multivariable analysis, no factor remained statistically significant after adjustment. Although duration of hypertension had the largest adjusted odds ratio (OR=2.056; 95% CI=0.948–4.456), the association did not reach statistical significance (p=0.068).